2014
DOI: 10.1039/c4ra01387e
|View full text |Cite
|
Sign up to set email alerts
|

Unexplored reactivity of 2-oxoaldehydes towards Pictet–Spengler conditions: concise approach to β-carboline based marine natural products

Abstract: Novel reactions under Pictet-Spengler conditions between tryptophan methyl ester/tryptamine and 2-oxoaldehydes have been developed and successfully utilized for the total synthesis of Merinacarboline (A and B), Eudistomin Y1, Pityriacitrin B, Pityriacitrin, Fascaplysin and analogues.2-Oxoaldehydes (OA) are among a few precursors that have been used extensively to synthesize a large variety of heterocyclic compounds. 1 Pictet-Spengler is one of the various reactions reported on OA leading to the synthesis of b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…The most powerful of these, arguably, is the Pictet‐Spengler and Bischlere‐Napieralski condensations 14 . For pityriacitrin alkaloids, five total synthetic routes have been described in the literature 7,14,16,21,26 . Zhu and co‐workers developed an elegant method that could direct the synthesis of diverse natural products bearing β ‐carboline from simple and readily available aromatic ketones and tryptamine derivatives in one‐pot 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The most powerful of these, arguably, is the Pictet‐Spengler and Bischlere‐Napieralski condensations 14 . For pityriacitrin alkaloids, five total synthetic routes have been described in the literature 7,14,16,21,26 . Zhu and co‐workers developed an elegant method that could direct the synthesis of diverse natural products bearing β ‐carboline from simple and readily available aromatic ketones and tryptamine derivatives in one‐pot 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the results of the above study, it was envisaged to check the generality of this strategy for the synthesis of β-carboline linked benzothiophene derivatives. Accordingly, we employed 1-acetyl-β-carboline 5 [ 67 68 ] for Claisen–Schimdt condensation with 2-nitrobenzaldehyde ( C ) in the presence of Cs 2 CO 3 and anhydrous THF at room temperature. Product 5C was obtained as a major product along with some unidentified impurities.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Ahmed et al [12] reported unexplored multicoupled domino reactions for the total synthesis of marinacarboline and analogs.…”
Section: Chemistrymentioning
confidence: 99%